Comparative Characteristics of Surgical Treatment and Balloon Aortic Valvuloplasty in Infants with Critical Aortic Stenosis - E. Imanov; Y. Truba; I. Dzyurii; O. Pliska; V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2019)
Critical aortic stenosis (AS) in infants is a complex pathology requiring emergency care. Treatment for such patients is a challenging problem. The methods of treatment include balloon valvuloplasty and open surgical valvuloplasty.The objective of the work is to analyze actual experience of surgical treatment and balloon valvuloplasty of critical aortic stenosis in infants.Materials and methods. For the period from 2006 to 2018, 58 infants with aortic stenosis were treated at the National Amosov Institute of Cardiovascular Surgery. Of these, 47 (81%) patients (Group 1) had balloon valvuloplasty of the aortic stenosis and 11 (19%) patients (Group 2) had surgical treatment.Results and discussion. After balloon valvuloplasty, there was significant reduction in the pressure gradient on the aortic valve in patients of the Group 1, as well as increase in the left ventricular ejection fraction; however, in the medium-term follow-up, the aortic valve pressure gradient increased in most patients, and aortic insufficiency began to increase. After surgical repair, good immediate and medium-term outcomes were observed in terms of the pressure gradient on the aortic valve and the degree of insufficiency.Conclusion. Surgical as well as balloon valvuloplasty are effective methods of AS treatment in infants with good immediate outcomes. The study suggests that balloon valvuloplasty may be an acceptable alternative to surgical treatment in patients in critical condition with signs of severe heart failure, but is associated with the increase in aortic insufficiency in long-term follow-up.